I must be living twice new & selected poems, 1975-2014 - Myles, Eileen 1949- (Ecco, An Imprint of HarperCollinsPublishers, 2016)
A collection of thrilling verse, including both new poems and beloved favorites, from the celebrated poet, modern cult icon, and author of Chelsea Girls. Eileen Myles' work is known for its blend of reality and fiction, the sublime and the ephemeral. Her work opens readers to astonishing new considerations of familiar places, like the East Village in her iconic Chelsea Girls, and invites them into lush--and sometimes horrid--dream worlds, imbuing the landscapes of her writing with the vividness and energy of fantasy. I Must Be Living Twice brings together selections from the poet's previous work with a set of bold new poems that reflect her sardonic, unapologetic, and fiercely intellectual literary voice. Steeped in the culture of New York City, Myles' milieu, I Must Be Living Twice is a prism refracting a radical world and a compelling life